Intensified and controllable vaporization of phase-changeable nanodroplets induced by simultaneous exposure of laser and ultrasound - Zhang, Qi (2024)
Phase-changeable contrast agents have been proposed as a next-generation ultrasound contrast agent over conventional microbubbles given its stability, longer circulation time and ability to extravasate. Safe vaporization of nanodroplets (NDs) plays an essential role in the practical translation of ND applications in industry and medical therapy. In particular, the exposure parameters for initializing phase change as well as the site of phase change are concerned to be controlled. Compared to the traditional optical vaporization or acoustic droplet vaporization, this study exhibited the potential of using simultaneous, single burst laser and ultrasound incidence as a means of activating phase change of NDs to generate cavitation nuclei with reduced fluence and sound pressure. A theoretical model considering the laser heating, vapor cavity nucleation and growth was established, where qualitative agreement with experiment findings were found in terms of the trend of combined exposure parameters in order to achieve the same level of vaporization outcome. The results indicate that using single burst laser pulse and 10-cycle ultrasound might be sufficient to lower the exposure levels under FDA limit for laser skin exposure and ultrasound imaging. The combination of laser and ultrasound also provides temporal and spatial control of ND vaporization and cavitation nucleation without altering the sound field, which is beneficial for further safe and effective applications of phase-changeable NDs in medical, environmental, food processing and other industrial areas.